δβγ-ENaC is inhibited by CFTR but stimulated by cAMP in Xenopus laevis oocytes - Rauh, Robert; Hörner, Christian; Korbmacher, Christoph (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2017)
The epithelial sodium channel (ENaC) and the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel critically regulate airway surface liquid by driving fluid absorption and secretion, respectively. Their functional interplay is complex and incompletely understood. ENaC is a heteromeric channel with three well-characterized subunits (α, β, and γ). In humans, an additional δ-ENaC subunit exists in lung and several other tissues, where it may replace the α-subunit to form δβγ-ENaC. Little is known about the physiological role of δβγ-ENaC and its possible interaction with CFTR. The aim of the present study was to investigate the effect of human CFTR on human δβγ-ENaC heterologously expressed in Xenopus laevis oocytes. In oocytes coexpressing δβγ-ENaC and CFTR the ENaC-mediated amiloride-sensitive whole cell current (ΔIami) was reduced by 50% compared with that measured in oocytes expressing δβγ-ENaC alone. Moreover, basal level of proteolytic ENaC activation was reduced in the presence of CFTR. The inhibitory effect of CFTR on δβγ-ENaC was due to a combination of decreased average open probability (Po) and reduced channel expression at the cell surface. Interestingly, in oocytes expressing δβγ-ENaC, increasing intracellular [cAMP] by IBMX and forskolin increased ΔIami by 50%. This stimulatory effect was not observed for human and rat δβγ-ENaC and was independent of CFTR coexpression and coactivation. Experiments with a mutant channel (δβS520Cγ-ENaC) which can be converted to a channel with a Po of nearly 1 suggested that cAMP activates δβγ-ENaC by increasing Po In conclusion, our results demonstrate that δβγ-ENaC is inhibited by CFTR but activated by cAM
EVALuna2:4526